2018
DOI: 10.1016/j.molstruc.2017.11.090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of dextran sulphate sodium in aqueous environment

Abstract: License: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Dextran-sulphate and similar polysaccharides are quite water soluble. In a study by Yu et al [45], data on a theoretical study of the molecular structure of sodium dextran sulfate in aqueous solutions, using the Merck Molecular Force Field method, were published. The authors found that various dextran sulfate oligomers in aqueous solutions were strongly solvated and existed in the form of spirals.…”
Section: Resultsmentioning
confidence: 99%
“…Dextran-sulphate and similar polysaccharides are quite water soluble. In a study by Yu et al [45], data on a theoretical study of the molecular structure of sodium dextran sulfate in aqueous solutions, using the Merck Molecular Force Field method, were published. The authors found that various dextran sulfate oligomers in aqueous solutions were strongly solvated and existed in the form of spirals.…”
Section: Resultsmentioning
confidence: 99%
“…GLYCAM-06j-1 forcefield [ 30 ] was used for DS topological parameters and the general amber forcefield (GAFF) [ 31 , 32 ] was used for SDS and TA topological parameters. An α-1,6 linked dodecamer was simulated for the BSA/DS simulations, due to its experimental molecular weight and high percentage of α-1,6 linkages [ 33 ]. Partial atomic charges for each IP agent were ascertained through the residual electrostatic potential fitting method [ 34 ], using the Hartree–Fock level with the 6–31G* basis set in Gaussian 0 9 [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…95%) with occasional branching occurring as 1,2-, 1,3-, and 1,4-linkages. The glucose residues are mainly disulfated: 2,3-disulfonation is most common, while 3,4- and 2,4-disulfonation occur relatively at lower proportions. , DS was modeled using Glycan Reader and Modeler. DS was modeled as a linear decamer of α-1,6-linked d -glucose , with 2,3-disulfonation at all residues except 2,4-disulfonation at residue 3 and 3,4-disulfonation at residue 6.…”
Section: Methodsmentioning
confidence: 99%
“…72,73 DS was modeled using Glycan Reader and Modeler. 74−76 DS was modeled as a linear decamer of α-1,6linked D-glucose 72,73 with 2,3-disulfonation at all residues except 2,4-disulfonation at residue 3 and 3,4-disulfonation at residue 6.…”
Section: T H I S C O N T E N T I S O N L Y L I C E N S E D F O R C O ...mentioning
confidence: 99%